Fixed or Flexible : Getting the Exchange Rate Right in the 1990s. (Economic Issues; Economic Issues ;, 1998)
This paper examines the recent evolution of exchange rate policies inthe developing world. It looks at why so many countries have made a transition from fixed or "pegged" exchange rates to "managed floating"currencies. It discusses how economies perform under different exchangerate arrangements, issues in the choice of regime, and the challenges poised by a world of increasing capital mobility, especially when bankingsectors are inadequately regulated or supervised.